A new event generator for PIPlus control systems - Merigo, L.; Beschi, M.; Padula, Fabrizio; Visioli, A. (2016)
© 2016 IEEE.In this paper we propose a new event detector for control systems with a PIplus controller. Its main feature is its capability of filtering the noise in a very effective way, by generating a quantized signal. Practical guidelines are given for the selection of the parameters. Simulation results show the efficacy of the technique and that it outperforms the use of standard use of a Butterworth low-pass filter.